EVALUATION OF SCHISTOSOMA MANSONI MORBIDITY ONE YEAR AFTER PRAZIQUANTEL TREATMENT IN RHINO CAMP AND OBONGI IN WEST NILE, UGANDA - Odongo-Aginya, E. I.; Lakwo, T. L.; Doehring, Med. Ekkehard (African Journal of Infectious Diseases (AJID), 2010)
An evaluation study on reversibility of Schistosoma mansoni induced periportal fibrosis (PF) morbidity following treatment with praziquantel, 40mg/kg body weight after one year, was carried out in Rhino Camp and Obongi all are West Nile districts in northern Uganda. To assess the reversibility of Schistosoma (S) mansoni induced PFs morbidity following treatment with praziquantel, 40mg/kg body weight after one year. The design was a Prospective cohorts study; and the setting was a busy canoe landing sites along Albert Nile in Schistosoma (S) mansoni hyperendemic areas of Rhino Camp and Obongi fishing village were selected for the study. Previously in 2005, 1562 people including fishermen and women, school pupils, teachers, and civil servants were studied in both fishing villages for S. mansoni using Kato/Katz stool smear method. Abdominal ultrasonography and sonomorphological abnormalities of periportal fibrosis were performed with Aloka portable ultrasound machine (Hellige, Freiburg, Germany) fitted with a convex probe of 3.5 mega Hertz was also performed in the field clinic on all patients who had S. mansoni eggs in their faeces. The sonomorphological abnormalities of periportal fibrosis were categorised and organomorphometry of liver and spleen was done. One thousand two hundred and seventy three 1273 (81.5%) patients in Rhino Camp and Obongi fishing villages were found to be excreting from 100 to â‰¥ 500 eggs per gram (epg) of faeces of S. mansoni eggs. Two hundred and eighty nine (18.5%) did not have eggs of S.mansoni in their faeces. All the 1273 patients secreting eggs of S.mansoni in their stool in Rhino Camp and Obongi fishing villages had abdominal ultrasonography and sonomorphological abnormalities of periportal fibrosis. Eight hundred and forty 840 (66%) although excreted S. mansoni eggs in their stool had Pf (0); Pf grade (I), n=259 (20.3%); Pf grade (II) n =147 (11.5%); and Pf grade (III) n=27 (2.1%) were observed.